Methylated miRNAs may serve as potential biomarkers and therapeutic targets for hidradenitis suppurativa. (12th October 2022) - Radhakrishna, U.; Ratnamala, U.; Jhala, D.D.; Vadsaria, N.; Patel, M.; Uppala, L.V.; Vishweswaraiah, S.; Vedangi, A.; Saiyed, N.; Damiani, G.; Jemec, G.B.E.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease influenced by genetics, non‐genetic and environmental factors that modulate miRNA expression. Currently, no miRNA data are available for HS. In this study, we profiled DNA methylation patterns of miRNA genes associated with HS susceptibility. Objectives: Identify miRNA gene methylation profiles associated with HS susceptibility. This study examined the methylation patterns of DNAs from 24 healthy controls and 24 patients with HS using Illumina Infinium MethylationEPIC BeadChip array analysis. Methylation patterns of miRNA genes were analysed using KEGG pathway analysis to explore the inversely correlated pathways regulated by miRNAs. Results: We identified 60 CpG sites representing 65 unique microRNA genes including 54 hypomethylated and 6 hypermethylated CpGs as potentially associated with HS. Some of these CpGs were found to be critical for skin function, such as miR‐29, miR‐200, miR‐205, miR‐548 and miR‐132. The miR‐192 is implicated in non‐alcoholic fatty liver disease. The miR‐200c gene was identified as a vital determinant in regulating skin repair after injury and may contribute to age‐associated alterations in wound repair. miR‐132 was significantly upregulated during the inflammation phase of wound repair, enhancing the activity of STAT3 and ERK pathways that promote keratinocyte proliferation. Conclusions: Epigenetically altered microRNA genes are implicated in wound healing, inflammation, keratinocyte proliferation and wound modulation. This is the first study to analyse methylation profiles of miRNA genes in the HS population, highlighting the unique role that miRNAs might play in diagnosing and treating HS.